2013
DOI: 10.4103/2231-0738.119853
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coptic Orthodox Christian church fasting on healthy and diabetic subjects

Abstract: Background and Aim: Coptic Orthodox Christian (COC) diet is unique in that it regularly interchanges between an omnivorous to a vegetarian type of diet, through four fasting periods over the course of the ecclesiastical year. Several studies have described its dietary regulations, however, its possible involvement in health is lacking. The aim of the present study is to detect the metabolic changes during COC fasting. Subjects and Methods: Seventy two devout Orthodox Christian fasters, 25 of whom were diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…These types of foods have pre-Christian origin as they used to be eaten by all Egyptians in ancient times; poor and wealthy as they were considered part of the traditional Egyptian diet as it is mentioned above (Wassef 1971). Thus, the diet of Coptic Orthodox Christian is rich in whole-grain bread, beans and sesame (Morcos et al 2013).…”
Section: Diet and Food Habits In Coptic Egyptmentioning
confidence: 99%
See 1 more Smart Citation
“…These types of foods have pre-Christian origin as they used to be eaten by all Egyptians in ancient times; poor and wealthy as they were considered part of the traditional Egyptian diet as it is mentioned above (Wassef 1971). Thus, the diet of Coptic Orthodox Christian is rich in whole-grain bread, beans and sesame (Morcos et al 2013).…”
Section: Diet and Food Habits In Coptic Egyptmentioning
confidence: 99%
“…Fish is also eaten in certain fasts to ease the length of the Coptic fast which is for about 200 days of the year. These types of food are eaten by all Egyptians as they have pre-Christian origin (Morcos et al 2013) Coptic ritual food habits have been inherited from one generation to another for about twenty centuries which helped in forming the current Coptic diet. That is, the Coptic food habits and liturgical foods show continuity of ancient food habits as the fertile rich soil and temperate climate conditions of Egypt have helped in diversifying the agricultural crops such as cereals, vegetables, legumes and fruits.…”
Section: Introductionmentioning
confidence: 99%
“…Sesame seeds are also rich in minerals (calcium, iron, phosphorus) and vitamins (vitamin A, thiamine, and riboflavin) (Obiajunwa, 2005). Sesame seeds are consumed as food, as well as in pharmaceutical and chemical industries (Hwang, 2005;Namiki, 2007) due to their high therapeutic and nutritional values (Liu et al, 2011;Morcos et al, 2013;D'Souza et al, 2016;Dissanayake et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Fasting, the willful partial or total abstention from restricted foods in many religions [2,6]. Research studies in Seventh-day Adventists [7], Greek Orthodox Church [8], and Egyptian Copts [9] have shown that religious fasting could play favorable health benefits. Different from the EOC-fasting episodes, the Greek Orthodox Church [10] and other studies [11,12] allow the faithful to consume seafood and fishes.…”
Section: Introductionmentioning
confidence: 99%